2019
DOI: 10.1088/1361-6560/ab3fb5
|View full text |Cite
|
Sign up to set email alerts
|

Towards continuous-to-continuous 3D imaging in the real world

Abstract: Imaging systems are often modeled as continuous-to-discrete mappings that map the object (i.e. a function of continuous variables such as space, time, energy, wavelength, etc) to a finite set of measurements. When it comes to reconstruction, some discretized version of the object is almost always assumed, leading to a discrete-to-discrete representation of the imaging system. In this paper, we discuss a method for single-photon emission computed tomography (SPECT) imaging that avoids discrete representations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 45 publications
(54 reference statements)
0
8
0
Order By: Relevance
“…More recently, we observed that SPECT LM emission data containing the energy attribute contains information to jointly estimate the activity and attenuation distributions [13]. Also, several studies have shown that LM data can yield improved reconstruction and quantification compared to binned data in SPECT imaging [14,15,16,17,18,19]. These investigations motivate the use of SPECT LM data containing the energy attribute for ASC.…”
Section: Introductionmentioning
confidence: 79%
“…More recently, we observed that SPECT LM emission data containing the energy attribute contains information to jointly estimate the activity and attenuation distributions [13]. Also, several studies have shown that LM data can yield improved reconstruction and quantification compared to binned data in SPECT imaging [14,15,16,17,18,19]. These investigations motivate the use of SPECT LM data containing the energy attribute for ASC.…”
Section: Introductionmentioning
confidence: 79%
“…The results from this study also motivate the development of methods to jointly estimate activity and attenuation distribution using only the SPECT emission data, especially if the computational requirements of processing LM data can be reduced. Efforts in the direction of reducing these computational requirements are currently underway [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…For some recent results, see Caucci. 32 A long review article on radiation dose and risk for imaging with ionizing radiation 27 provides a general review of methods of computing image-quality metrics as a function of radiation dose. This paper also develops several new graphical methods for depicting the tradeoffs among radiation dose, image quality and patient risk.…”
Section: Photon Counting and Photon Processingmentioning
confidence: 99%